PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN - Titi Nurfitri; Sri Lestari (Faculty of Economics and Business Universitas Jenderal Soedirman, 2009)
The research is entitled “The Effect of Leadership and Motivation towards Employees Performance ( A Comparative Study at RSUD Banyumas, RS Sinar Kasih, PT.PLN and PDAM Banyumas Regency). The limitation on research problems are: 1) Research at RSUD Banyumas couldn’t be done because of difficulties in getting the data, 2) The research was carried out during August till September 2009.The research has the aims to find out and analyze:1) The effect of tranformational, transactional and laissez faire leadership towards employees motivational Sinar Kasih Hospital (Private Company), PT. PLN (Persero (BUMN), and PDAM (BUMD). 2) The effect of transformational, transactional and laissez faire leadership towards employees performance at Sinar Kasih Hospital (Private Company), PT. PLN (Persero (BUMN), and PDAM (BUMD). 3) The effect of motivation towards employees performance at Sinar Kasih Hospital (Private Company), PT. PLN (Persero (BUMN), and PDAM (BUMD). 4) The leadership applied at Sinar Kasih Hospital (Private Company), PT. PLN (Persero (BUMN), and PDAM (BUMD) among transformational, transactional and laissez faire leadership. The research populations are all employees who work at the research object companies with the sample is as minimum as 20% selected randomly. The method of analysis is Multiple Regression Analysis Method. The research populations are all employees who work at the research object companies with the sample is as minimum as 20% selected randomly. The method of analysis is Multiple Regression Analysis Method.The result of research analysis shows that:1. In total transformational, transactional, and laissez faire leadership have an effect on employees motivation and performance at RS Sinar Kasih Purwokerto.2. At PT.PLN (Persero) APJ Purwokerto, in total transformational, transactional, and laissez faire leadership only have an effect on employees job motivation3. In PDAM (BUMD) Banyumas Regency in total transaformational, transactional and laissez faire leadership have an effect on employees motivation and performance.4. Based on research analysis, it can be found that the leadership style applied at RS Sinar Kasih Purwokerto and PT. PLN (APJ) Purwokerto and PT. PLN (APJ) Purwokerto is transformational style and PDAM (BUMD) Banyumas Regency applies transactional style. Finally the result of research implies that:1. Even in total transformational, transactional and laissez faire leadership give significant effect towards employees motivation and performance, but for themanagement of RS Sinar Kasih it can focus on increasing its motivation and performance through the application of transformational leadership style.2. Transformational, transactional and laissez faire leadership styles at PT.PLN (Persero) Purwokerto give an effect on job motivation but it cannot increase employees performance. For this purpose the management of PT.PLN (Persero) APJ Purwokerto must pay attention on the leadership style applied by the company so far.3. The existence of transformational, transactional and laissez faire leadership in affecting employees motivation and performance at PDAM Banyumas Regency must get management attention to maintain and increase leader’s potency available so far.